100 SQL server mistakes and how to avoid them - Carter, Peter A. (Manning Publications, 2025)
100 SQL server mistakes and how to avoid them prepares you for the pitfalls database professionals often encounter-from administration to development, availability, and security. You'll learn to sidestep common errors that slow down your T-SQL code and ensure your SQL Server is installed and configured to handle anything your organization throws at it.